47.8k views
0 votes
If f(x) = -5x - 1 and g(x) =√x - 6 , what is (f * g)(2)

User Mike Wade
by
5.1k points

1 Answer

2 votes

Answer:

(f * g)(2) = -11√2 +66

Explanation:

Points to remember

Let f(x) and g(x) be the two functions, then (f * g) can be written as,

(f * g) = [f(x)][g(x)]

To find the value of (f * g)(2)

we have,

f(x) = -5x - 1 and g(x) =√x - 6

f(2) = -5*2 - 1 = -11

g(2) = √x - 6 = √2 - 6

(f * g)(2) = [f(2)][g(2)]

= -11 (√2 - 6)

= -11√2 +66

Therefore (f * g)(2) = -11√2 +66

User Amom
by
5.4k points